Ex vivo SIV-specific CD8 T cell responses in heterozygous animals are primarily directed against peptides presented by a single MHC haplotype. - Justin M Greene; Emily N Chin; Melisa L Budde; Jennifer J Lhost; Paul J Hines; Benjamin J Burwitz; Karl W Broman; Jennifer E Nelson; Thomas C Friedrich; David H O'Connor (PLoS ONE, 2012)
The presence of certain MHC class I alleles is correlated with remarkable control of HIV and SIV, indicating that specific CD8 T cell responses can effectively reduce viral replication. It remains unclear whether epitopic breadth is an important feature of this control. Previous studies have suggested that individuals heterozygous at the MHC class I loci survive longer and/or progress more slowly than those who are homozygous at these loci, perhaps due to increased breadth of the CD8 T cell response. We used Mauritian cynomolgus macaques with defined MHC haplotypes and viral inhibition assays to directly compare CD8 T cell efficacy in MHC-heterozygous and homozygous individuals. Surprisingly, we found that cells from heterozygotes suppress viral replication most effectively on target cells from animals homozygous for only one of two potential haplotypes. The same heterozygous effector cells did not effectively inhibit viral replication as effectively on the target cells homozygous for the other haplotype. These results indicate that the greater potential breadth of CD8 T cell responses present in heterozygous animals does not necessarily lead to greater antiviral efficacy and suggest that SIV-specific CD8 T cell responses in heterozygous animals have a skewed focus toward epitopes restricted by a single haplotype.